STUDENTS MISCONCEPTION IDENTIFICATION OF CHEMICAL CANDIDATES TEACHERS USING THREE TIER TEST METHOD IN THE BASIC CONCEPT OF CHEMICAL BOND - Napsin Palisoa; Dominggus Tahya; Victor Kayadoe (EDU SCIENCES JOURNAL, 2020)
Misconceptions possessed by prospective chemistry teacher students greatly affect the learning process when teaching in class, because the information or concepts conveyed to students are misconceptions. Prospective chemistry teacher students who experience misconceptions are simply reduced, because if a long misconception is left in the memory of the student there is a resistant misconception, namely a strong misconception that is difficult to reduce and constantly occurs. To find out whether the concepts stored in the memory of prospective chemistry teacher students, misconceptions need to be detected using the diagnostic three-tier test method. Diagnostic three-tier test method consists of 3 tiers, tier 1 is the choice of answers, tier 2 choices of reasons, and the third tier is the choice of the level of confidence of the answers and reasons. Diagnostic three-tier test method can detect misconceptions owned by students with the category of misconception 1 (M1), misconception 2 (M2), and misconception 3 (M3). The MK1 category students have the right answer choices, the wrong reason choices, but have the right beliefs, the M2 category students have the wrong answer choices, the right reason choices, but have the right beliefs, while the M3 category of students have the wrong answer choices, the wrong reason choices, but have confidence right. Detection test results using three-tier diagnostic methods, obtained from 32 students who took the test there are (28) 87% of chemistry teacher candidates experienced misconceptions (M1, M2, and M3). Prospective chemistry teacher students who have detected misconceptions on the basic concepts of chemical bonds need to be corrected, so that after graduating from college they do not bring misconceptions to students while teaching. Students' misconceptions can be reduced using an integrated 3R conceptual change (recall, recognition, and reintegration) (CC3R) strategy